Intraoperative radiotherapy for head and neck cancer. Experiences with low-energy photons – preliminary results - Rutkowski, Tomasz; Składowski, Krzysztof (Contemporary Oncology/Współczesna Onkologia, 2008)
Intraoperative radiation therapy (IORT) due to precise application of a high radiation dosage to the target area with minimal exposure of surrounding normal tissue is often used for head and neck cancer. From 2003 to 2006 a new IORT technique using the PRS 400 – Photon Radiosurgery System (Carl Zeiss Surgical GmbH) INTRABEAM generating low energy photons was applied in 16 patients with early-stage oral cancer in the Cancer Centre – Maria Sklodowska-Curie Memorial Institute in Gliwice. After 20 months median time of follow-up no recurrences or increased acute mucosal reaction was observed. Advantages and limitations of the method are discussed in comparison to other IORT techniques. Due to the unique physical and radiobiological characteristics the method seems to be promising in radical treatment of NGiSz and may be considered as an alternative boost technique for early stage oral cancer.